The impact of H1N1 influenza on acute respiratory infection in pre-school children in north east brazil. (4th April 2011) - Fawkner-Corbett, D; Rose, K; Fonceca, A; Bezerra, P; Britto, M; Correia, J; Duarte, M; Cuevas, L; Hopkins, M; McNamara, P S
Abstract : Introduction: Acute respiratory infection (ARI) is a major cause of mortality and morbidity in children, particularly in the developing world. In June 2009 the WHO declared a new strain of swine-origin H1N1 influenza virus as a pandemic. The aim of this study was to assess the impact of H1N1 on ARI presentations to A&E in preschool children over a year in a resource-poor setting in Brazil. Methods: Children <5 years presenting with symptoms of ARI to the A&E department at a hospital in North Eastern Brazil between April 2009 and March 2010 were recruited following parental consent. Clinical data and nasopharyngeal aspirates were collected from each child. Samples were transported to UK where Multiplex PCR was used to detect 18 different viral or atypical bacterial respiratory pathogens, including H1N1. Results: Samples were collected from 223 children from a resource-poor setting. 57% (127/223) were subsequently hospitalised and at least one pathogen was detected in 91.5% (204/223) of samples. The most commonly detected pathogens were Adenovirus (36%; n=80), Bocavirus (35%; n=78), Respiratory Syncytial Virus (18%; n=41), Rhinovirus (18%; n=41) and Influenza (15%; n=34). Influenza cases peaked during November 2009 with 79% (27/34) being H1N1 subtype. Co-infection was found frequently with 50% (111/223) participants being found positive for more than one pathogen. Co-infection with H1N1 was particularly common (78%) with Adenovirus and Bocavirus being the most common pathogens co-detected. Children with H1N1 infection were more likely to be admitted to hospital than those without H1N1 infection (78 vs 54%; p=0.021). At its peak, H1N1 was detected in approximately 20% of preschool children recruited to this study and attending A&E with ARI. Conclusions: We have described particularly high rates of pathogen detection (91.5%) and co-infection (50%) compared to the published literature. Over the year, H1N1 was the fifth commonest virus detected. H1N1 had a significant impact given that it was detected in 20% of hospitalised preschool children with ARI during the pandemic peak.